2018
DOI: 10.3389/fmicb.2018.02813
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Response to Therapy for Nontuberculous Mycobacterial Lung Disease: Quo Vadis?

Abstract: Assessing progression of disease or response to treatment remains a major challenge in the clinical management of nontuberculous mycobacterial (NTM) infections of the lungs. Serial assessments of validated measures of treatment response address whether the current therapeutic approach is on track toward clinical cure, which remains a fundamental question for clinicians and patients during the course of NTM disease treatment. The 2015 NTM Research Consortium Workshop, which included a patient advisory panel, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“… 37 , 38 The lack of responsiveness of the EQ-5D-3L scores to sputum culture status is noteworthy, given that sputum culture samples are regarded as the primary biomarkers for assessing treatment efficacy in this population. 12 , 39 These findings are in line with Hong et al, who also reported that the EQ-5D-3L index scores were unable to distinguish between MAC-LD patients and healthy controls. 11 Previous studies assessing the responsiveness of EQ-5D-3L in other respiratory conditions, such as COPD and asthma, also conclude that the EQ-5D-3L is better suited to detecting change in moderate-to-severe patients, with limited responsiveness in mild disease states.…”
Section: Discussionsupporting
confidence: 81%
“… 37 , 38 The lack of responsiveness of the EQ-5D-3L scores to sputum culture status is noteworthy, given that sputum culture samples are regarded as the primary biomarkers for assessing treatment efficacy in this population. 12 , 39 These findings are in line with Hong et al, who also reported that the EQ-5D-3L index scores were unable to distinguish between MAC-LD patients and healthy controls. 11 Previous studies assessing the responsiveness of EQ-5D-3L in other respiratory conditions, such as COPD and asthma, also conclude that the EQ-5D-3L is better suited to detecting change in moderate-to-severe patients, with limited responsiveness in mild disease states.…”
Section: Discussionsupporting
confidence: 81%
“…MAC disease treatment typically extends 12 months past culture conversion and routinely requires 18 months to complete ( 21 ). Evaluating MAC responses to treatment also relies on qualitative or semiquantitative tests (e.g., sputum culture and radiography) and clinical assessments (e.g., reductions in MAC-related symptoms and improvements in quality-of-life measurements), which have limited utility for evaluating treatment success ( 22 ). Notably, a substantial fraction of patients with MAC disease still exhibit symptoms and radiographic findings consistent with MAC PD after treatment completion, and ⩾50% of these patients have subsequent NTM-positive respiratory cultures within 12–36 months ( 23 ), suggesting that they have residual disease after treatment completion.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, in light of the challenges associated with the diagnosis of NTM pulmonary disease, monitoring response to treatment is also difficult [26]. Current approaches centre upon serial measurement of sputum culture, radiological findings and clinical symptoms over months to assess whether a patient is "on track" for a curative response.…”
Section: Diagnosismentioning
confidence: 99%